(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
this paper introduces a new created program application built based on MATLAB programing language to solve power system networks at steady state problems, which include power flow studies with significant approach. The load flow solution uses iterative techniques that are namely, Newton-Raphson, Gauss-Seidel and Fast Decouple. After obtaining their results, line changes like line switching, tap changer and bus changing such as bus deletion or any specific information at the same bus can be easily achieved. Moreover, the users can enter their own system, and save it to apply the pervious analysis. This friendly interactive program designed to be simple for the users with accurate results and it can be applied for any network.